2023
DOI: 10.3389/fnmol.2022.1105278
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing microRNA editing and mutation sites in Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder whose pathogenesis is still unclear. MicroRNAs (miRNAs) are a kind of endogenous small non-coding RNAs that play important roles in the post-transcriptional regulation of genes. Recent researches show that miRNAs are edited in multiple ways especially in central nervous systems. A-to-I editing of RNA catalyzed by Adenosine deaminases acting on RNA (ADARs) happens intensively in brain and is also noticed in other organs and tissues. Although miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…We identified 1025 M/E sites with significant editing levels by analyzing 176 sRNA-seq profiles of ccRCC patients (n = 154) and healthy controls (n = 22). The M/E sites at the 3 end accounted for the majority, which was consistent with previous work 37 , 40 , 43 , 56 59 . We identified 122 editing events with significantly different editing levels in ccRCC samples compared to healthy control samples.…”
Section: Discussionsupporting
confidence: 92%
“…We identified 1025 M/E sites with significant editing levels by analyzing 176 sRNA-seq profiles of ccRCC patients (n = 154) and healthy controls (n = 22). The M/E sites at the 3 end accounted for the majority, which was consistent with previous work 37 , 40 , 43 , 56 59 . We identified 122 editing events with significantly different editing levels in ccRCC samples compared to healthy control samples.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al [42] identified 122 miRNA editing sites of different types that were differentially edited in clear cell renal cell carcinoma. In neurological diseases [43] , [44] , [31] , there are also hundreds of miRNA editing sites with different editing levels compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, mice lacking SREB2 exhibited an opposite phenotype [15]. Genetic variants of SREB2 were also described as risk factors for schizophrenia [16] and autism spectrum disorder [17]. SREB3 was proposed to function as a receptor for the pentapeptide gonadotropin-releasing hormone (GnRH-(1-5)), as well as for a novel reproductive peptide known as phoenixin-20 amide (PNX).…”
Section: Introductionmentioning
confidence: 99%